Understanding Communication Experience between Teacher and Student with Visual Impairment in the formation of self- concept - Kholita Putri Arifiana; Wiwid Noor Rakhmad, M.Si (Interaksi Online, 2016)
Student with visual impairnment are children who have limited eyesight so he was not able to learn something by looking at it directly. Blind students enriching experiences through the rest of its senses. They can not understand exactly an abstract concept. Limitations sense of vision experienced by visually impaired students bring a certain impact inside the blind. The impact what happens to students is one of the emergence of certain properties shown their students as a way to show his existence. That if left unchecked will affect the students' self-concept for what could be done to encourage students into the negative behavior that will form a negative self concept anyway. This study uses qualitative descriptive type with a phenomenological approach. This study seeks to explain how the communication experience of teachers and students with visual impairment in the formation of self-concept. This study uses the Coordinated Management theory that explains how the meaning of the stages of delivering a message to a message can be interpreted together. Based on the research results indicate that a teacher has to understand that blindness can lead their particular behaviors that can affect the self-concept of the blind students. Communication problems experienced by teachers in educating the blind is on how so that students can interpret the exact message delivered even without involving the sense of sight. How do teachers in providing knowledge and the formation of self-concept in visual impairment was with verbal explanations orally using easily understood language blind students. Intonation is also important to note because the intonation blind students will easily understand the emotions interlocutors. The communication process teachers and students with visual impairment in build self-concept is make approach with students, then understand character each student to understand the positive and negative of these students then provide guidance or counseling if negative behaviors begin to emerge.